The Inner Dimension of the Orthodox Tradition and Traditionalism According to André Scrima's Hermeneutics - Tătaru-Cazaban, Bogdan (Review of ecumenical studies, 2020)
A unique Figure in the Orthodox Church, André Scrima was a bridge-personality among Christians and between Christianity and other religions. In his early works, bearing witness to a "spiritual inheritance" and a "blessing of grace" that he had personally received, he stressed the inner dimension of Eastern Christianity represented by Hesychastic spirituality - a perennial divine inspiration manifested across history. But both as a spiritual figure and a professor of comparative religion, he oriented his reflection toward considering the religious plurality of the world from a Christian perspective. Searching for the "lieu théologal" of hospitality for others' spiritualities became one of the main purposes of Scrima's reflections which occasionally dealt in a sympathetic as well as critical manner with Traditionalism. This paper aims to highlight the interest raised by an Orthodox reflection on the so-called "esoteric" side of his Tradition which leads to a hermeneutic of religious diversity.